Training Preparing Mother’s Breastfeeding Realize, Understand and Upgrade Your Child’s Mpasi Needs to Posyandu Kader - Luluk Damayanti; Melati Putri Utami; Reynandar Wilda Muhammad; Umi Rahmawati; Wimpy Wimpy; Enny Listiawati (Jurnal Peduli Masyarakat, 2020)
Inappropriate feeding to infants and children can lead to malnutrition, stunting and even death. The aim of this PKMD is to increase the knowledge of mothers in practicing breastfeeding and complementary foods to posyandu cadres in Cangkol village. The problem of stunting can be balanced by offering solid. MPASI must pay attention to the recommended Nutritional Adequacy Rate (RDA) based on the age group and the texture of the food according to the age development of children under five. MPASI is said to meet the requirements if it contains carbohydrates, proteins, fats and vitamin. The purpose of this article is to provide education to the community in Cangkol village, about breastfeeding and breastfeeding. MPASI according to the age of the toddler. The extension method is carried out by lectures, questions and answers and demonstrations. The Village Community Health Counseling program activity with the title of training to prepare mother's breast milk (realize, understand and upgrade your toddler's needs) to posyandu cadres in Cangkol Village, Mojolaban, Sukoharjo smoothly, as evidenced by the mothers understanding the material presented during education.